RETRACTED: High Glucose Activated Cardiac Fibroblasts by a Disruption of Mitochondria-Associated Membranes - Zhang, Ling-Yu; Lin, Rui-Ting; Chen, Hao-Ran; Yang, Yong-Cong; Lin, Meng-Fei; Tian, Lei-Gang; Pan, Zhi-Qiong; Lin, Lin; Zhu, Liang-Liang; Gu, Zhen-Jie; Chen, Xue-Wen; Li, Yu-Jing; et al. (Frontiers in Physiology, 2021)
Cardiac fibrosis is evident even in the situation without a significant cardiomyocyte loss in diabetic cardiomyopathy and a high glucose (HG) level independently activates the cardiac fibroblasts (CFs) and promotes cell proliferation. Mitochondrial respiration and glycolysis, which are key for cell proliferation and the mitochondria-associated membranes (MAMs), are critically involved in this process. However, the roles and the underlying mechanism of MAMs in the proliferation of HG-induced CFs are largely unknown. The proliferation and apoptosis of CFs responding to HG treatment were evaluated. The MAMs were quantified, and the mitochondrial respiration and cellular glycolytic levels were determined using the Seahorse XF analyzer. The changes of signal transducer and activator of transcription 3 (STAT3) and mitofusin-2 (MFN2) in responding to HG were also determined, the effects of which on cell proliferation, MAMs, and mitochondrial respiration were assessed. The effects of STAT3 on MFN2 transcription was determined by the dual-luciferase reporter assay (DLRA) and chromatin immunoprecipitation (CHIP). HG-induced CFs proliferation increased the glycolytic levels and adenosine triphosphate (ATP) production, while mitochondrial respiration was inhibited. The MAMs and MFN2 expressions were significantly reduced on the HG treatment, and the restoration of MFN2 expression counteracted the effects of HG on cell proliferation, mitochondrial respiration of the MAMs, glycolytic levels, and ATP production. The mitochondrial STAT3 contents were not changed by HG, but the levels of phosphorylated STAT3 and nuclear STAT3 were increased. The inhibition of STAT3 reversed the reduction of MFN2 levels induced by HG. The DLRA and CHIP directly demonstrated the negative regulation of MFN2 by STAT3 at the transcription levels via interacting with the sequences in the MFN2 promoter region locating at about −400 bp counting from the start site of transcription. The present study demonstrated that the HG independently induced CFs proliferation via promoting STAT3 translocation to the nucleus, which switched the mitochondrial respiration to glycolysis to produce ATP by inhibiting MAMs in an MFN2-depression manner.